Adolescent boys with constitutional delay of growth and puberty grow faster than patients with organic growth hormone deficiency. (10th November 2020) - Binder, Gerhard; Lehrian, Theresa J.; Hoffmann, Elisa; Blumenstock, Gunnar; Rahmaoui, Abdelkader; Trzaskoma, Benjamin; Reinehr, Thomas
Abstract: Objective: Constitutional delay of growth and puberty (CDGP) is a tempo variant with a good prognosis. Healthy late‐maturing adolescents grow slower than postulated by age‐related references, and therefore, CDGP is frequently confused with growth hormone deficiency (GHD). For differential diagnosis, height velocity references for CDGP are needed. Design and Patients: Here, we provide height velocity data for late‐maturing boys based on mixed longitudinal and cross‐sectional observations in a group of 38 German adolescents with proven CDGP and compare them with cross‐sectional observations in a group of 164 adolescents with organic GHD from the National Cooperative Growth Study registry. Results: In the critical age interval from 13.4 to 14.9 years, the growth of prepubertal adolescents with CDGP was faster (mean/median height velocity, 5.2/5.4 cm/years; quartiles, 4.4‐6.2 cm/years) than that of prepubertal adolescents with organic GHD (3.5/3.2 cm/years; quartiles, 2.0‐4.4 cm/years) in the cross‐sectional analysis ( p < .0001). Based on our mixed longitudinal and cross‐sectional analysis, the height velocity of adolescent boys with CDGP exceeded previous model calculations on average by 1.0 cm. Conclusions: In conclusion, prepubertal adolescents with CDGP grow faster than patients with organic GHD. Previous model estimates underestimated height velocity of boys with CDGP.